Analysis Analysis of Da’wah Management in the Organization of the Mujahadah Nihadlul Mustaghfirin Religious Gathering Conducted by Gus Arwan Maulana in Ambokulon Village - Attiya Elmaulida; Siti Prihatiningtyas (Institut Agama Islam Negeri (IAIN) Curup, 2026)
Purpose − Da’wah management is an important element in ensuring the sustainability and effectiveness of religious activities at the community level, especially Mujahadah recitations, which play a strategic role in the spiritual development of congregations. This study aims to determine the implementation of the Nihadlul Mustaghfirin Mujahadah recitation and analyze the application of da’wah management functions in these activities Method − This study is a qualitative study with a descriptive approach. The novelty of this research lies in the combination of the functions of da’wah management and mujahadah practices carried out in the Mujahadah Nihadlul Mustaghfirin study group led by local figures, which has still been relatively empirically studied. Data collection was conducted through field observations, in-depth interviews, and documentation using primary and secondary data sources. Data analysis used the Miles and Huberman model, which includes the stages of data collection, data reduction, data presentation, and conclusion drawing Findings − The result of the study show that the recitation is managed in a planned and structured manner through a clear division of roles among the administrators, active involvement of the congregation, systematic time and material management, and a continuous evaluation mechanism. Gus Arwan Maulana’s leadership plays a significant role in building motivation, loyalty, and continuity of congregation participation. This study concludes that the application of effective da’wah management can improve the quality of mujahadah recitation sessions and have a positive impact on strengthening the spirituality and unity of the community.